Trees and Watershed Management in Karamoja, Uganda - Mbogga, Michael; Malesu, Maimbo; de Leeuw, Jan (Evidence on Demand, 2014)
Karamoja is a dryland sub-region in north-east Uganda. Having suffered historical injustices, it now faces many difficulties, including civil and administrative challenges. Karamoja performs poorly on development indicators compared to other parts of Uganda: 82% of its population lives under the poverty line. Its infrastructure is underdeveloped, and the subregion is troubled by climate variability and climate change. Drought and shifts in weather result in low agricultural productivity and declining rural production systems. Floods and droughts have had a particularly detrimental effect. Moreover, Karamoja faces increasing environmental degradation, further threatening crop and livestock production. Trees are at the heart of Karamoja’s ecology, providing livelihoods and nutrition for livestock and people when all else fails; trees also provide Karamoja with fundamental ecosystem services. Thus there is a need for evidence about the role that trees play in Karamoja. This document looks at trees in watershed management in the sub-region. Efficient water management may provide a large part of the solution to the current poor livelihood prospects in Karamoja. From consultation with experts and a literature review, there is wide evidence of the benefits that trees confer to communities in Karamoja. We see various options for action with respect to trees in watershed management: the use of trees for flash flood control; erosion control and waterway fixation; resilient crop production; resilient livestock production; and efficient utilization of green water -- the precipitation that falls on the land, which does not run off into rivers, dams or groundwater but is absorbed into the soil. Karamoja experiences frequent flash floods caused by water from heavy rains running from higher to lower lying areas. These can devastate lives and property, often sweeping away houses and farmlands. Ground-covering vegetation and trees can significantly reduce occurrence of flash floods. Trees allow for the infiltration of water into the soil. Therefore, this review strongly advises higher tree coverage in Karamoja’s crop fields and rangelands. Another benefit of trees is that they reduce erosion. They intercept rainfall, reducing the force with which drops strike the soil. Rainfall on bare land makes soil compact. The pores in the soil, which normally absorb the water, close; as a result, rainfall, instead of soaking into the soil, turns into runoff that often carries away valuable top soil, silting up streams, rivers and dams. This, in turn, harms the proper streaming of water. This review strongly recommends the maintenance, planting and regeneration of trees along riverbanks to control erosion. Water management focuses on availability of blue water, the fresh surface and groundwater found in lakes, rivers or aquifers. While blue water is important, this review advises that green water is equally important. Most rainwater that falls goes to the creation of biomass. Green water is especially valuable for crop growth and livestock production, since it is easily taken up by biomass through the soil. The use of trees needs to be mainstreamed in watershed management planning. Currently, many water resource management plans exist. An objective should be that watershed management organizations include trees in their planning. We advise that DFID develop capacity in organizations responsible for water management.